Lwowskie spotkania Zdzisława Jachimeckiego z Ignacym Janem Paderewskim - Woźna-Stankiewicz, Małgorzata (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
Based on manuscript and printed sources, the meetings of Zdzisław Jachimecki with Ignacy Paderewski in Lviv in 1901, 1902, 1910 and in Rome in 1925 are presented for the first time in the literature on the great pianist. Jachimecki’s radio readings about Paderewski, broadcast in 1928, 1945 and 1946, as well as a speech by the Krakow musicologist in Lviv on December 16, 1935, dedicated to him, are discussed. An unknown letter from Paderewski to Jachimecki of March 4, 1936 was quoted.